Terapia de reminiscencia para mejorar la memoria del adulto mayor del hogar “Estancia de Paz” Francisco Valdivieso del barrio Landangui de la parroquia Malacatos del cantón Loja, en el período marzo–julio 2015 - Vega Sarango, Yadyra Maribel (2015)
The present thesis entitled: REMINISCENCE THERAPY TO IMPROVE ELDERLY PEOPLE MEMORY AT "ESTANCIA DE PAZ" NURSING HOME FRANCISCO VALDIVIESO LOCATED AT LANDANGUI NEIGHBORHOOD MALACATOS PARISH - LOJA CANTON, IN THE PERIOD MARCH-JULY 2015, was developed with the purpose ofHelp to what the elderly peopleimproves their memory, since the difficulty the same that bring as a consequence memory decrease in short-term, the difficulty in performing familiar tasks, difficulty in language, disorientation of time and place,changes in mood, finally they neglect their hygiene and nutrition.The general objective: To improve elderly people memory through the Reminiscence Therapy at “Estancia de Paz” HomeFrancisco Valdivieso located at Landangui neighborhood Malacatos parish - Loja canton, in the period March-July 2015.The research work is part of action research model; through an intervention period, this research topic has been approached from a descriptive and explanatory study, with a mixed approach in other words qualitative and quantitative;the research were basedon three areas: theoretical assessment, design and implementation of the alternative; the methods and development and evaluation of the effectiveness of the strategy, the methods used were:the scientific, synthetic, inductive, hermeneutical, dialectical, which allowed to make the discussion and comparison of the alternatives proposed.The technique used was theMMSE (Folstein) 1 test, to assess the level of memory which wasapplied to the six elderly.Finally concludes that, more than half of beneficiaries improved their memory, for that reason Reminiscence Therapy is recommended for the elderly population